Optimizing Outcomes: Bevacizumab with Carboplatin and Paclitaxel in 5110 Ovarian Cancer Patients-A Systematic Review and Meta-Analysis - Yu Jin Kim; Hee Min Lee; Ga Eun Lee; Jin Hui Yoo; Hwa Jeong Lee; Sandy Jeong Rhie (MDPI AG, 2024)
Background/Objectives: The study aimed to evaluate the efficacy and safety of incorporating bevacizumab into the combination therapy of carboplatin and paclitaxel for epithelial ovarian cancer and other clinical applications. Methods: A systematic review was conducted following PRISMA guidelines using keyword searches in PubMed, Embase, Cochrane Library, CINAHL, ClinicalTrials.gov, and ICTRP until February 2024. Randomized controlled trials (RCTs) comparing carboplatin and paclitaxel with and without bevacizumab in ovarian cancer patients were included. Efficacy outcomes were overall survival (OS) and progression-free survival (PFS), as described by hazard ratios (HRs). Safety outcomes were analyzed with risk ratios (RRs) for 16 adverse events. Results: Seven RCTs (n = 5110) were included. The combination with bevacizumab significantly improved PFS (HR: 0.73; 95% confidence interval: 0.58, 0.92; p = 0.008). The chemotherapy group receiving bevacizumab with carboplatin and paclitaxel showed a significantly higher incidence of hypertension, non-CNS bleeding, thromboembolic events, GI perforation, pain, and proteinuria. Conclusions: The combination of carboplatin, paclitaxel, and bevacizumab improves PFS compared to the regimen without bevacizumab, but it raises significant safety concerns. Clinical management should consider adverse event prevention by vigilantly monitoring blood pressure, signs and symptoms of bleeding, thromboembolism, GI perforation, and pain to balance the therapeutic benefits with the potential risks of this combination therapy.